A solid waste fluid backfill material and its preparation and performance control method

By using solid waste matrix materials composed of construction solid waste materials, industrial waste slag curing agents and fly ash, combined with comprehensive performance regulators, the performance of fluid backfills is regulated, and the problems of unstable performance of existing fluid backfills and high consumption of curing agents are solved, and solid waste fluid backfills with controllable strength and excellent performance are achieved to meet the needs of diversified engineering applications.

CN119080469BActive Publication Date: 2025-04-04HUANGSHAN UNIV +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411585873.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-04
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The working and mechanical properties of existing fluid backfills are unstable. The cement used in curing agents has problems such as high resource consumption, high energy consumption and high pollution emissions. There is a lack of special admixtures suitable for fluid backfills. The preparation method lacks reasonable and effective ratio optimization and performance regulation.

Method used

The solid waste matrix material composed of construction solid waste materials, industrial waste slag curing agents and fly ash is used, combined with comprehensive performance regulators such as polycarboxylic acid-based water reducing agents, and the optimal mix ratio and water-solid ratio are determined through orthogonal tests to regulate the performance of fluid backfillers.

Benefits of technology

The strength of solid waste flow backfiller is controlled in the range of 0.6-12MPa, with excellent working performance and stable performance, meeting the needs of diversified engineering applications, reducing engineering costs, and achieving the development goals of low-carbon, environmentally friendly, economical and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119080469B_ABST
    Figure CN119080469B_ABST
Patent Text Reader

Abstract

The invention discloses a solid waste fluid backfill material and a preparation and performance control method thereof, which relates to the technical field of green low-carbon geotechnical materials. The solid waste fluid backfill material is formed by uniformly stirring a solid waste matrix material, water and a comprehensive performance regulator. By changing the mixing ratio of the solid waste matrix material, the water-solid ratio and the amount of recycled fine aggregate and other parameters to control the performance of the solid waste fluid backfill material, a fluid backfill material with controllable strength in the range of 0.6-12MPa, excellent working performance and stable performance can be prepared, which meets the diversified engineering application needs, reduces engineering costs, and achieves the low-carbon, environmentally friendly, economical and efficient development goals of backfill engineering in the construction field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of green low-carbon geotechnical materials, and in particular to a solid waste fluid backfill material and a preparation method and performance control method thereof. Background Art

[0002] At present, industrial solid waste emissions are large, the comprehensive utilization rate is low, a large amount of land is occupied, and risks such as environmental pollution are caused. There is an urgent need to find effective ways to utilize it on a large scale.

[0003] In the process of building and transportation infrastructure construction, it is inevitable to encounter construction conditions of filling projects. These filling projects are mostly constructed by compacting and backfilling plain soil or gray soil. However, for backfill projects such as foundation pit fertilizer troughs, pipeline trenches, and roadbed three-back, they often face construction difficulties such as small construction sites, narrow backfill space, and limited special-shaped spaces, resulting in unstable backfill soil compaction quality and difficulty in meeting design requirements. As a result, cases such as uneven settlement of roadbeds and pipeline subsidence damage often occur. Therefore, in order to ensure the quality of backfill and speed up the progress of the construction period, some projects often use plain concrete instead of plain soil and gray soil for backfilling, which leads to a significant increase in construction costs.

[0004] Fluidized backfill material is a low-carbon geotechnical engineering material developed in recent years. It is directly poured by chutes, pumps, etc., and uses its fluidity and self-compacting properties to achieve effective backfilling, reducing the compaction process of traditional plain soil and gray soil backfilling. It solves the problems of long backfilling cycle, high labor costs, and difficulty in ensuring backfilling quality in backfill projects in the construction field. It can also realize the resource recycling of large amounts of solid waste and has irreplaceable technical advantages in engineering applications. At present, the fluidized backfill materials used in engineering projects are mixed with soil, curing agent, water and admixtures in a certain proportion. The soil materials are mostly engineering slag, waste sludge, etc., and their physical and chemical properties have a great influence on the fluidized backfill materials, resulting in unstable working performance and mechanical properties of the fluidized backfill materials; the curing agent is mostly cement or a mixture of cement and industrial solid waste. The cement dosage is large and the cost is high. The curing effect on slag and sludge with high water content is poor. In addition, cement production has the disadvantages of high resource consumption, high energy consumption, and high pollution emissions. Therefore, its application is limited; the admixtures used in the fluidized backfill materials are basically the same as concrete admixtures, mainly water reducers, early strength agents and retarders, but the types and components of these admixtures are not completely suitable for fluidized backfill materials, and the performance adjustment effect on the fluidized backfill materials is limited. Therefore, there is a lack of special admixtures suitable for fluidized backfill materials. In addition, fluidized backfill materials have a wide range of application scenarios, and different engineering application scenarios have different performance requirements for fluidized backfill materials. Currently, the preparation of fluidized backfill materials still lacks reasonable and effective ratio optimization and performance control methods, which is obviously not conducive to its promotion and application in actual engineering. Therefore, it is necessary to propose performance control methods from multiple aspects such as material system and performance requirements.

[0005] In view of the technical problems existing in the preparation of the above-mentioned fluidized backfill material, the inventors, based on their many years of engineering experience and professional theoretical knowledge in the field of such materials, have developed a solid waste fluidized backfill material and a method for its preparation and performance regulation through technological innovations in the resource utilization of construction solid waste and industrial solid waste and the comprehensive application of admixtures. Summary of the invention

[0006] In view of the above technical problems, the present invention provides a solid waste fluid backfill material and a method for preparing and controlling the performance thereof.

[0007] Technical solution: A solid waste fluid backfill material is formed by uniformly stirring solid waste matrix material, water and comprehensive performance regulator;

[0008] The solid waste matrix material is composed of construction solid waste material, industrial waste slag curing agent and fly ash;

[0009] The construction solid waste material is one of recycled micro powder and recycled fine aggregate or a combination of the two;

[0010] The industrial waste slag solidifying agent comprises the following components in parts by weight: 20-30 parts of carbide slag powder, 55-70 parts of slag powder, 5-10 parts of steel slag powder, 5-10 parts of desulfurized gypsum, 2-4 parts of nano-alumina, and 2-4 parts of calcium sulfoaluminate;

[0011] The comprehensive performance regulator comprises the following components in parts by weight: 65-85 parts of polycarboxylic acid water reducer, 5-10 parts of diethanol monoisopropanolamine, 5-10 parts of sodium citrate, 2-8 parts of maltodextrin, 3-6 parts of sodium silicate, 2-5 parts of sodium castor oil sulfonate, and 1-2 parts of sodium hydroxide.

[0012] Furthermore, the recycled micro powder is a construction solid waste material with a particle size of less than 0.075 mm formed by crushing and grinding waste concrete; the recycled fine aggregate is a construction solid waste material with a particle size range of 0.075-4.75 mm formed by crushing and grinding waste concrete.

[0013] Furthermore, the preparation method of the industrial waste residue solidifying agent is as follows:

[0014] S1: Dry, grind and select four kinds of industrial waste residues, namely carbide slag, ore slag, steel slag and power plant gypsum, to obtain carbide slag powder, ore slag powder, steel slag powder and desulfurized gypsum, with a particle size distribution range of 1-30um;

[0015] S2: evenly mix carbide slag powder, slag powder, steel slag powder and desulfurized gypsum;

[0016] S3: Add nano-alumina and calcium sulfoaluminate powder, mix thoroughly and evenly to obtain the industrial waste slag solidifying agent.

[0017] Furthermore, the preparation method of the comprehensive performance regulator is as follows:

[0018] S1: uniformly mix the polycarboxylic acid water reducer, diethanol monoisopropanolamine and sodium castor oil sulfonate solution, heat to 35-45°C, fully stir and ultrasonically oscillate for 5-10 minutes to obtain a mixed solution A;

[0019] S2: dissolving NaOH powder in water to prepare a 0.001 mol / L NaOH solution, mixing sodium citrate, sodium silicate and maltodextrin powders, adding the mixture to the NaOH solution, and placing the mixture in an ultrasonic mill for ultrasonic dispersion for 10-15 min. After dispersion and dissolution, uniformly stirring for 5-10 min to obtain a mixed solution B;

[0020] S3: uniformly mix the mixed solution A and the mixed solution B obtained above, fully stir and then ultrasonically vibrate for 8-15 minutes to obtain the comprehensive performance regulator.

[0021] Furthermore, the fly ash is fine ash discharged and collected from coal-fired power plants, and its standard grade is not lower than level two.

[0022] A method for preparing and controlling the performance of a solid waste fluid backfill material comprises the following steps:

[0023] S1: solid waste matrix material composed of recycled micropowder, industrial waste slag solidifying agent and fly ash, water and comprehensive performance regulator are used to prepare solid waste fluid backfill material, wherein the total mass of the solid waste matrix material is 100, wherein the mass ratio of recycled micropowder, industrial waste slag solidifying agent and fly ash is 76-88:6-12:6-12, the water-solid ratio (the mass ratio of water to solid waste matrix material) is 0.20-0.26, and the dosage of the comprehensive performance regulator is 1.0%-2.0% of the mass of the solid waste matrix material;

[0024] The optimal mix ratio of the solid waste matrix material components and the reasonable range of the water-solid ratio are determined by orthogonal test; the orthogonal test comprises the following steps:

[0025] S11: The dosage of comprehensive performance regulator is fixed, the dosage of industrial waste slag solidifier and fly ash as well as water-solid ratio are set in a gradient manner, and the orthogonal test method is used to design the mix ratio of multiple groups of solid waste fluid backfill material samples;

[0026] S12: according to the designed mix ratio, weigh corresponding amounts of recycled micro powder, industrial waste slag curing agent and fly ash, mix them evenly, add them into a mortar mixer, then add corresponding amounts of water, stir evenly to obtain a mixture C, add corresponding amounts of comprehensive performance regulator into the mixture C, continue to stir evenly to obtain the solid waste fluid backfill material;

[0027] S13: first, the fluidity of each group of solid waste fluid backfill materials is tested, and then each group of solid waste fluid backfill materials is respectively loaded into a cylindrical mold, and after curing for 28 days, a solidified sample of the solid waste fluid backfill material is obtained, and the compressive strength of each group of solidified samples is respectively tested;

[0028] S14: Compare and analyze the measured fluidity and compressive strength with the design values ​​of fluidity and compressive strength, and comprehensively determine the optimal mix ratio of the solid waste matrix material and the reasonable value range of the water-solid ratio;

[0029] S2: When the maximum compressive strength of the solid waste fluid backfill material prepared by S1 is still lower than the design compressive strength value, then on the basis of the optimal mix ratio of the sample determined by S1, the solid waste fluid backfill material is re-prepared by partially or completely replacing the recycled micro powder with recycled fine aggregate, and the replacement rate of recycled fine aggregate is set at a gradient; the fluidity and compressive strength of the solid waste fluid backfill material samples under different recycled fine aggregate replacement rates are measured, the influence of the recycled fine aggregate replacement rate on the performance of the solid waste fluid backfill material is analyzed, and the reasonable value range of the recycled fine aggregate replacement rate is comprehensively determined;

[0030] S3: When the maximum compressive strength of the solid waste fluid backfill material still cannot meet the design compressive strength value after being replaced by recycled fine aggregate in S2, the dosage of the industrial waste slag solidifying agent in the solid waste matrix material is gradually increased on the basis of the optimal mix ratio determined in S2, and the water-solid ratio is gradually reduced until the compressive strength and fluidity of the solid waste fluid backfill material meet the corresponding design values;

[0031] S4: After the compressive strength and fluidity of the solid waste fluid backfill material are adjusted to meet the corresponding design values ​​in step S3, the initial setting time, final setting time and water seepage of the solid waste fluid backfill material are regulated by gradiently changing the dosage of the comprehensive performance regulator.

[0032] Preferably, S11 selects the industrial waste slag solidifying agent dosage of 6%, 8%, 10% and 12% of the total mass of the solid waste matrix material, the fly ash dosage of 6%, 8%, 10%, 12% of the total mass of the solid waste matrix material, the water-solid ratio of 0.20, 0.22, 0.24, 0.26, the comprehensive performance regulator dosage is fixed at 1.5%, and 16 groups of solid waste fluid backfill material samples with different mix ratios are obtained by orthogonal experimental design.

[0033] Preferably, the replacement rate of recycled fine aggregate in S2 increases gradually from 10% to 100%; the interval is 10% as a gradient.

[0034] Preferably, the dosage of the industrial waste slag solidifying agent in S3 increases by 1% and the water-solid ratio decreases by 0.005.

[0035] Preferably, the amount of the comprehensive performance regulator in S4 is increased by a gradient of 0.25%. Beneficial Effects

[0036] (1) The large-scale utilization of solid waste matrix materials such as construction solid waste (recycled micropowder, recycled fine aggregate), industrial waste slag curing agent, fly ash, etc. to prepare and produce solid waste fluid backfill can effectively solve the problem of large-scale stacking of construction waste and industrial waste slag, reduce the pollution to the environment caused by the accumulation of large amounts of solid waste, and achieve effective coordination between engineering construction and comprehensive utilization of solid waste.

[0037] (2) By changing the mix ratio of solid waste matrix materials, water-to-solid ratio, recycled fine aggregate content and other parameters to regulate the performance of solid waste fluidized backfill materials, a fluidized backfill material with controllable strength in the range of 0.6-12 MPa, excellent working performance and stable performance can be prepared, which meets the diversified engineering application needs, reduces engineering costs, and achieves the low-carbon, environmentally friendly, economical and efficient development goals of backfill projects in the construction field.

[0038] (3) The comprehensive performance regulator prepared by the present invention can significantly enhance the anti-segregation, anti-shrinkage and compressive strength of the solid waste fluid backfill material, and can effectively adjust the fluidity and coagulation time of the solid waste fluid backfill material, thus playing an important role in improving the working performance and mechanical properties of the solid waste fluid backfill material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a solid waste fluid backfill solidification sample;

[0040] Figure 2 Scanning electron microscope image of the solidified sample of solid waste fluid backfill material to meet the optimal mix ratio of application scenario 1;

[0041] Figure 3 Scanning electron microscope image of the solidified sample of solid waste fluid backfill material to meet the optimal mix ratio of application scenario 2;

[0042] Figure 4 Scanning electron microscope image of the solidified sample of solid waste fluid backfill material to meet the optimal mix ratio of application scenario 3. DETAILED DESCRIPTION

[0043] The present invention will be described in detail below with reference to the accompanying drawings. Example

[0044] The solid waste fluid backfill material is prepared by using solid waste matrix materials consisting of recycled micro powder or recycled fine aggregate, industrial waste slag solidifying agent and fly ash, water and comprehensive performance regulator.

[0045] The preparation methods of each material are as follows:

[0046] (1) Recycled micro powder is a construction solid waste material with a particle size of less than 0.075 mm, which is obtained by crushing and grinding waste concrete;

[0047] (2) Recycled fine aggregate is a construction solid waste material with a particle size range of 0.075-4.75 mm, which is obtained by crushing and grinding waste concrete.

[0048] (3) The preparation method of industrial waste slag solidifying agent is as follows:

[0049] S1: Dry, grind and select four kinds of industrial waste residues, namely carbide slag, ore slag, steel slag and power plant gypsum, to obtain carbide slag powder, ore slag powder, steel slag powder and desulfurized gypsum, with a particle size distribution range of 1-30um;

[0050] S2: evenly mix carbide slag powder, slag powder, steel slag powder and desulfurized gypsum;

[0051] S3: Add nano-alumina and calcium sulfoaluminate powder, mix thoroughly and evenly to obtain the industrial waste slag solidifying agent.

[0052] (4) The preparation method of the comprehensive performance regulator is as follows:

[0053] S1: uniformly mix the polycarboxylic acid water reducer, diethanol monoisopropanolamine and sodium castor oil sulfonate solution, heat to 35-45°C, fully stir and ultrasonically oscillate for 5-10 minutes to obtain a mixed solution A;

[0054] S2: dissolving NaOH powder in water to prepare a 0.001 mol / L NaOH solution, mixing sodium citrate, sodium silicate and maltodextrin powders, adding the mixture to the NaOH solution, and placing the mixture in an ultrasonic mill for ultrasonic dispersion for 10-15 min. After dispersion and dissolution, uniformly stirring for 5-10 min to obtain a mixed solution B;

[0055] S3: uniformly mix the mixed solution A and the mixed solution B obtained above, fully stir and then ultrasonically vibrate for 8-15 minutes to obtain the comprehensive performance regulator.

[0056] (5) Fly ash refers to the fine ash collected from coal-fired power plants, and its standard grade is not lower than level 2.

[0057] In order to meet the needs of different engineering applications, three types of solid waste fluid backfill materials are prepared, which are suitable for three different engineering application scenarios.

[0058] Application scenario 1: Road subgrade backfill, which requires that the fluidity of solid waste backfill material should be greater than 160 mm, and the design value of 28d compressive strength should be no less than 1.2 MPa;

[0059] Application scenario 2: Backfilling of pipeline trenches under traffic roads requires that the fluidity of solid waste backfill material should be greater than 150mm, and the design value of 28d compressive strength should be no less than 6.5MPa;

[0060] Application scenario 3: The foundation cushion layer is required to be poured and backfilled, the fluidity of the solid waste backfill material is greater than 110mm, and the design value of the 28d compressive strength is not less than 10MPa.

[0061] Firstly, recycled micro powder, industrial waste slag solidifying agent, fly ash, water and comprehensive performance regulator are used to prepare solid waste fluid backfill material suitable for application scenario 1.

[0062] The optimal mix ratio of the solid waste matrix material components and the reasonable range of water-solid ratio are determined by orthogonal test, and the orthogonal test includes the following steps:

[0063] S1: The dosage of industrial waste slag solidifying agent is selected as 6%, 8%, 10% and 12% of the total mass of solid waste matrix materials, the dosage of fly ash is selected as 6%, 8%, 10% and 12% of the total mass of solid waste matrix materials, the water-solid ratio is 0.20, 0.22, 0.24 and 0.26, and the dosage of comprehensive performance regulator is fixed at 1.5%. Through the orthogonal test design group number, the commonly used three-factor four-level orthogonal table has 16 (4 ^3 ) and 16(4 ^5 ) orthogonal table, this embodiment uses 16 (4 ^3 ) The orthogonal table determines the mix ratio of 16 groups of solid waste fluid backfill material samples, as shown in Table 1;

[0064] S2: According to the mix ratio, weigh corresponding amounts of recycled micro powder, industrial waste slag solidifying agent and fly ash, mix them evenly, add them into a mortar mixer, then add corresponding amounts of water, stir evenly to obtain a mixture A, add corresponding amounts of comprehensive performance regulator into the mixture A, continue to stir evenly to obtain the solid waste fluid backfill material;

[0065] S3: First, the fluidity of 16 groups of solid waste fluid backfill materials was tested, and then the solid waste fluid backfill materials were respectively loaded into cylindrical molds, and solidified samples of solid waste fluid backfill materials were obtained after curing for 28 days (such as Figure 1 As shown in Table 1, the compressive strength of 16 groups of cured samples were tested respectively. The test results are shown in Table 1.

[0066] S4: Compare and analyze the fluidity and compressive strength measured above with the design values ​​of fluidity and compressive strength, and comprehensively determine the optimal mix ratio of the solid waste matrix material and the reasonable range of water-solid ratio.

[0067] Table 1 Mixing ratio and test results of solid waste fluid backfill material mixed with recycled micropowder

[0068]

[0069] Through the analysis of the above orthogonal test results, it can be seen that when the industrial waste slag curing agent dosage is 8-12% of the mass of the solid waste matrix material, the fly ash dosage is 6-12% of the mass of the solid waste matrix material, and the water-solid ratio is 0.24-0.26, the fluidity and compressive strength of the prepared solid waste fluid backfill material meet the requirements of application scenario 1. Under the premise of meeting the fluidity required by application scenario 1, when the industrial waste slag curing agent dosage is 12% of the mass of the solid waste matrix material, the fly ash dosage is 8% of the mass of the solid waste matrix material, and the water-solid ratio is 0.24 (No. 14), the 28d compressive strength of the solid waste fluid backfill material reaches the maximum value. The mix ratio at this time can be regarded as the optimal mix ratio. The microscopic image of the solidified sample of the solid waste fluid backfill material obtained by scanning electron microscopy is shown in the figure. Figure 2 shown.

[0070] The maximum 28d compressive strength of application scenario 1 is 3.95 MPa, which obviously does not meet the requirements of application scenario 2. In order to prepare solid waste fluid backfill that meets the requirements of application scenario 2, on the basis of the optimal mix ratio determined in Table 1, recycled fine aggregate is used to partially or completely replace the recycled micropowder to prepare solid waste fluid backfill. The replacement rate of recycled fine aggregate increases from 10% to 100%, with a gradient interval of 10%. The test mix ratio is shown in Table 2. The fluidity and compressive strength of the solid waste fluid backfill samples under different recycled fine aggregate replacement rates were measured, and the results are shown in Table 2. The influence of the recycled fine aggregate replacement rate on the performance of the solid waste fluid backfill is comprehensively analyzed, and the reasonable value range of the recycled fine aggregate replacement rate is determined.

[0071] Table 2 Mix ratio and test results of solid waste fluid backfill material mixed with recycled fine aggregate

[0072]

[0073] It can be seen from the test results in Table 2 that with the increase of the amount of recycled fine aggregate, the fluidity of the solid waste fluid backfill material decreases continuously, and its 28d compressive strength shows a trend of first increasing and then decreasing. When the recycled fine aggregate replacement rate is 60%-80%, the fluidity and compressive strength of the prepared solid waste fluid backfill material meet the requirements of application scenario 2. Under the premise of meeting the fluidity required by application scenario 2, when the recycled fine aggregate replacement rate is 70% (No. 7), the 28d compressive strength of the solid waste fluid backfill material reaches the maximum value. The mix ratio and recycled fine aggregate replacement rate at this time are determined as the optimal mix ratio. The microscopic image of the solidified sample of the solid waste fluid backfill material obtained by scanning electron microscopy is shown in the figure. Figure 3 shown.

[0074] The maximum 28d compressive strength of application scenario 2 is 8.3 MPa, which obviously does not meet the requirements of application scenario 3. In order to prepare solid waste fluid backfill material that meets the requirements of application scenario 3, based on the optimal mix ratio determined in Table 2, the dosage of industrial waste slag curing agent in the solid waste matrix material is increased, and the water-solid ratio is appropriately reduced, and the solid waste fluid backfill material is re-prepared. The test mix ratio and results are shown in Table 3.

[0075] Table 3 Mixing ratio and test results of solid waste fluid backfill material samples

[0076]

[0077] It can be seen from the test results in Table 3 that with the increase in the dosage of industrial waste slag solidifying agent, the fluidity of the solid waste fluid backfill material continues to decrease, and its 28d compressive strength gradually increases. Similarly, reducing the water-solid ratio can reduce the fluidity of the solid waste fluid backfill material and increase its strength. When the dosage of industrial waste slag solidifying agent is 17% of the total mass of the solid waste matrix material, the dosage of fly ash is 8% of the mass of the solid waste matrix material, and the water-solid ratio is 0.24 (No. 3), the fluidity and compressive strength of the solid waste fluid backfill material both meet the requirements of application scenario 3. At this time, the scanning electron microscope image of the solidified sample of the solid waste fluid backfill material is as follows: Figure 4 In addition, when the dosage of industrial waste slag solidifying agent is 15% of the total mass of solid waste matrix material, the dosage of fly ash is 8% of the total mass of solid waste matrix material, and the water-solid ratio is 0.22 (No. 5), the performance of the prepared solid waste fluid backfill material can also meet the requirements of application scenario 3.

[0078] Although the present invention has been disclosed as above in terms of preferred embodiments, they are not intended to limit the present invention. Anyone skilled in the art can make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection defined by the claims of this application.

Claims

1. A method for controlling the performance of solid waste fluid backfill material, characterized in that: The solid waste fluid backfill material is formed by uniformly stirring solid waste matrix material, water and a comprehensive performance regulator; The solid waste matrix material is composed of construction solid waste material, industrial waste slag curing agent and fly ash; The construction solid waste material is one of recycled micro powder and recycled fine aggregate or a combination of the two; The industrial waste slag solidifying agent comprises the following components in parts by weight: 20-30 parts of carbide slag powder, 55-70 parts of slag powder, 5-10 parts of steel slag powder, 5-10 parts of desulfurized gypsum, 2-4 parts of nano-alumina, and 2-4 parts of calcium sulfoaluminate; The comprehensive performance regulator comprises the following components in parts by weight: 65-85 parts of polycarboxylic acid water reducer, 5-10 parts of diethanol monoisopropanolamine, 5-10 parts of sodium citrate, 2-8 parts of maltodextrin, and 3-6 parts of sodium silicate. 2-5 parts of sodium castor oil sulfonate, 1-2 parts of sodium hydroxide; The recycled fine powder is a construction solid waste material with a particle size of less than 0.075 mm, which is obtained by crushing and grinding waste concrete; the recycled fine aggregate is a construction solid waste material with a particle size range of 0.075-4.75 mm, which is obtained by crushing and grinding waste concrete; The preparation method of the industrial waste residue solidifying agent is as follows: S1: Dry, grind and select four kinds of industrial waste residues, namely carbide slag, ore slag, steel slag and power plant gypsum, to obtain carbide slag powder, ore slag powder, steel slag powder and desulfurized gypsum, with a particle size distribution range of 1-30um; S2: evenly mix carbide slag powder, slag powder, steel slag powder and desulfurized gypsum; S3: adding nano-alumina and calcium sulfoaluminate powder, and mixing them thoroughly to obtain the industrial waste slag solidifying agent; The preparation method of the comprehensive performance regulator is as follows: S1: uniformly mix the polycarboxylic acid water reducer, diethanol monoisopropanolamine and sodium castor oil sulfonate solution, heat to 35-45°C, fully stir and ultrasonically oscillate for 5-10 minutes to obtain a mixed solution A; S2: dissolving NaOH powder in water to prepare a 0.001 mol / L NaOH solution, mixing sodium citrate, sodium silicate and maltodextrin powders, adding the mixture to the NaOH solution, and placing the mixture in an ultrasonic mill for ultrasonic dispersion for 10-15 min. After dispersion and dissolution, uniformly stirring for 5-10 min to obtain a mixed solution B; S3: uniformly mixing the mixed solution A and the mixed solution B obtained above, stirring them fully and then ultrasonically shaking for 8-15 minutes to obtain the comprehensive performance regulator; The fly ash is fine ash collected from coal-fired power plants, and its standard grade is not lower than level 2; The method for controlling the performance of the solid waste fluid backfill material comprises the following steps: S1: solid waste matrix material composed of recycled micro powder, industrial waste slag solidifying agent and fly ash, water and comprehensive performance regulator are used to prepare solid waste fluid backfill material, wherein the total mass of the solid waste matrix material is 100, wherein the mass ratio of recycled micro powder, industrial waste slag solidifying agent and fly ash is 76-88:6-12:6-12, the water-solid ratio is 0.20-0.26, and the dosage of the comprehensive performance regulator is 1.0%-2.0% of the mass of the solid waste matrix material; The optimal mix ratio of the solid waste matrix material components and the reasonable range of water-solid ratio are determined by orthogonal test; the orthogonal test comprises the following steps: S11: The dosage of comprehensive performance regulator is fixed, the dosage of industrial waste slag solidifier and fly ash as well as water-solid ratio are set in a gradient manner, and the orthogonal test method is used to design the mix ratio of multiple groups of solid waste fluid backfill material samples; S12: according to the designed mix ratio, weigh corresponding amounts of recycled micro powder, industrial waste slag curing agent and fly ash, mix them evenly, add them into a mortar mixer, then add corresponding amounts of water, stir evenly to obtain a mixture C, add corresponding amounts of comprehensive performance regulator into the mixture C, continue to stir evenly to obtain the solid waste fluid backfill material; S13: first, the fluidity of each group of solid waste fluid backfill materials is tested, and then each group of solid waste fluid backfill materials is respectively loaded into a cylindrical mold, and after curing for 28 days, a solidified sample of the solid waste fluid backfill material is obtained, and the compressive strength of each group of solidified samples is respectively tested; S14: Compare and analyze the measured fluidity and compressive strength with the design values ​​of fluidity and compressive strength, and comprehensively determine the optimal mix ratio of the solid waste matrix material and the reasonable value range of the water-solid ratio; S2: When the maximum compressive strength of the solid waste fluid backfill material prepared by S1 is still lower than the design compressive strength value, then on the basis of the optimal mix ratio of the sample determined by S1, the solid waste fluid backfill material is re-prepared by partially or completely replacing the recycled micro powder with recycled fine aggregate, and the replacement rate of recycled fine aggregate is set at a gradient; the fluidity and compressive strength of the solid waste fluid backfill material samples under different recycled fine aggregate replacement rates are measured, the influence of the recycled fine aggregate replacement rate on the performance of the solid waste fluid backfill material is analyzed, and the reasonable value range of the recycled fine aggregate replacement rate is comprehensively determined; S3: When the maximum compressive strength of the solid waste fluid backfill material still cannot meet the design compressive strength value after being replaced by recycled fine aggregate in S2, the dosage of the industrial waste slag solidifying agent in the solid waste matrix material is gradually increased on the basis of the optimal mix ratio determined in S2, and the water-solid ratio is gradually reduced until the compressive strength and fluidity of the solid waste fluid backfill material meet the corresponding design values; S4: After the compressive strength and fluidity of the solid waste fluid backfill material are adjusted to meet the corresponding design values ​​in step S3, the initial setting time, final setting time and water seepage of the solid waste fluid backfill material are regulated by gradiently changing the dosage of the comprehensive performance regulator.

2. The method for controlling the performance of the solid waste fluid backfill material according to claim 1, characterized in that: S11 selected the dosage of industrial waste slag solidifier as 6%, 8%, 10% and 12% of the total mass of solid waste matrix materials, the dosage of fly ash as 6%, 8%, 10% and 12% of the total mass of solid waste matrix materials, the water-solid ratio as 0.20, 0.22, 0.24 and 0.26, and the dosage of comprehensive performance regulator as fixed at 1.5%. The orthogonal experimental method was used to design 16 groups of solid waste fluid backfill material samples with different mix proportions.

3. The method for controlling the performance of the solid waste fluid backfill material according to claim 1, characterized in that: The replacement rate of recycled fine aggregate in S2 increases gradually from 10% to 100%; the interval is 10%.

4. The method for controlling the performance of the solid waste fluid backfill material according to claim 1, characterized in that: The dosage of industrial waste slag solidifying agent in S3 increases by 1% and the water-solid ratio decreases by 0.

005.

5. The method for controlling the performance of the solid waste fluid backfill material according to claim 1, characterized in that: The gradient increase of the dosage of the comprehensive performance regulator in S4 is 0.25%.

Citation Information

Patent Citations

  • Premixed liquid solidified soil

    CN107459301A